Implementation of State Civil Apparatus Policy in Indonesia - Selpiah Sappe; Dede Saidah (Institut Pemerintahan Dalam Negeri (IPDN), 2017)
This research is using Policy Implementation Theory from van Meter and van Horn which is consist of six indicators, namely Purpose and Target, Response of the Target group, Inter-organization communication, organization of implementor, Social, Economic and Politics conditions, and the source of policy. With using post-positivism approach and Qualitatif method, research result shows that the Implementation of State Apparatus is not optimum yet. There are several indicators are not implemented yet. Beside that, this research finds two major obstacles namely internal and exernal factors.